Analysing changes of the Poyang Lake water area using Sentinel-1 synthetic aperture radar imagery. Issue 23 (2nd December 2017) - Zeng, Lingfang; Schmitt, Michael; Li, Lin; Zhu, Xiao Xiang
ABSTRACT: Poyang Lake is the largest freshwater lake in China. Monitoring changes of its water area is essential for the conservation of important wetlands and ecological resources, and plays an important role for sustainable water use and management. Landsat and Moderate-Resolution Imaging Spectroradiometer (MODIS) sensor images are widely used for mapping waterbodies, because of their sensitivity for spectral reflectance of water. However, studies using Landsat images have limited their investigations of changes of Poyang Lake to dry season due to the impairment by cloud cover. Further limited by the rather long 16 day revisit cycle, most existing studies build on the vague assumption that Poyang Lake undergoes only relatively slow changes during this season. MODIS, in contrast, provides a very short revisit period, but has been proven not to be able to assess the water area of Poyang Lake accurately due to low spatial resolution. Therefore, the contribution of this study is to investigate recent Poyang Lake water area changes both during high- and low-water period with unforeseen temporal and spatial resolution using Sentinel-1 synthetic aperture radar (SAR) imagery. More specifically, we aim at investigating Poyang Lake's recent water area changes in intra-month scales. During the observation period from October 2014 to March 2016, October 2014 was the month with the largest max/min water coverage ratio. Water coverage of winter in 2014 and 2015 was completely different, as a severe drought happened in 2014 and an unusual winter flood happened in 2015. Thus, this study demonstrates the potential of using Sentinel-1 SAR data to reveal intra-month variations, benefiting from the sensor's regular observation capabilities independent of weather conditions. It is shown that Sentinel-1 SAR data, with rapid availability and free-of-charge distribution policy, as well as relatively high spatial and temporal resolutions, is becoming an indispensable data source for a detailed monitoring of important inland waterbodies and wetlands.